O planejamento urbano e a oferta de serviços públicos: o caso da cidade de Santarém Pará - MOURA, Samuel Ivan Oliveira (Universidade Federal do Oeste do Pará, 2023)
Urban planning is necessary for the efficient management of cities. The research aimed to identify the public problem regarding the urban equipment of the neighborhoods: Maracanã II, Old Airport, Center and Green Area, the research was guided through various visions of urban space, focusing on understanding the planning of cities, as well as geoprocessing to accelerate the process of collecting data from the urban clipping that was studied. The sectors that are contained in the study are: leisure (spaces of coexistence and sports practices), security (existing infrastructure that supports public safety agencies), health (basic units), education (schools, university center, etc.) and mobility (infrastructure of road coverings, routes and public transport waiting points). The diagnosis revealed the neighborhoods that have more infrastructure and those that have less. The Center – much because its historic occupation was prior to the others, with 100% asphalt roads and many urban equipment – while The Old Airport has a certain organization in the offers of public services (where the State Stadium is located, the Hospital Hemopa and the City hall of Santarém), Maracanã II being third because it has institutions distributed throughout the neighborhood – which because it is contemplated with an urban beach has paved roads, hypothesis revealed in the research. And the Neighborhood Área Verde, the furthest from the shopping center, with the lowest offer of services from all sectors surveyed. The results showed that the theme is relevant to the interests of local society, which allow a current reading of various aspects that can be used for the benefit of the city and, consequently, its residents.